This Divided Island : Stories from the Sri Lankan War - Subrabainain, Samanth (Gurgaon : Penguin Groups, 2014)
In the summer of 2009, the leader of the dreaded Tamil Tiger guerrillas was killed, bringing to a bloody end the stubborn and complicated civil war in Sri Lanka. For nearly thirty years, the war's fingers had reached everywhere: into the bustle of Colombo, the Buddhist monasteries scattered across the island, the soft hills of central Sri Lanka, the curves of the eastern coast near Batticaloa and Trincomalee, and the stark, hot north. With its genius for brutality, the war left few places, and fewer people, untouched. What happens to the texture of life in a country that endures such bitter conflict? What happens to the country's soul? Samanth Subramanian gives us an extraordinary account of the Sri Lankan war and the lives it changed. Taking us to the ghosts of summers past, and to other battles from other times, he draws out the story of Sri Lanka today - an exhausted, disturbed society, still hot from the embers of the war. Through travels and conversations, he examines how people reconcile themselves to violence, how religion and state conspire, how the powerful become cruel, and how victory can be put to the task of reshaping memory and burying histories.This Divided Island is a harrowing and humane investigation of a country still inflamed
Keywords: History -- Sri Lanka 1983-2009